THE EFFECT OF THE USE OF INTERACTIVE VIDEO LEARNING MEDIA ON THE SCIENCE LEARNING OUTCOMES OF GRADE IV STUDENTS OF STATE ELEMENTARY SCHOOL 040470 LINGGA JULU - Sinuraya, Nisa Kelnia Br; Muliani, Eti; Sembiring, Wisno Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Background: The use of interactive learning media is important in improving students’ understanding, especially in IPAS learning that contains abstract concepts such as energy transformation. At SD Negeri 040470 Lingga Julu, several students still had difficulty understanding IPAS material through conventional teaching methods. Objective: This study aimed to determine the effect of using interactive video learning media on the IPAS learning outcomes of fourth-grade students at SD Negeri 040470 Lingga Julu . Methods: This study used a quantitative, quasi-experimental design with a pretest-posttest control group. The sample consisted of 30 fourth-grade students, divided into an experimental class of 15 and a control class of 15. The experimental class learned using interactive video media, while the control class learned through conventional teaching. Data were collected using a multiple-choice test consisting of 20 valid and reliable items. The data were analyzed using normality and homogeneity tests, and an independent-samples t-test in SPSS version 22. Results: The experimental class's average score increased from 56.33 in the pretest to 92.67 in the posttest. Meanwhile, the control class obtained an average posttest score of 79.40. The independent-samples t-test showed a p-value of 0.000 < 0.05, indicating a significant difference between the experimental and control classes. Conclusion: Interactive video learning media had a significant positive effect on students’ IPAS learning outcomes. This media helped students understand energy transformation material more effectively than conventional teaching methods.